Poly(ethylene glycol) based bis-diol as a functional medium for highly efficient conversion of urea and methanol to dimethyl carbonate. Issue 3 (17th September 2015) - Zhang, Zhaofu; Zhang, Lujun; Wu, Congyi; Qian, Qingli; Zhu, Qinggong; Han, Buxing
Abstract : Poly(ethylene glycol) based bis-diol/ZnO is an excellent catalytic system for the reaction of urea and methanol to produce DMC. The equilibrium yield of DMC in the reaction can be ten times higher than that of the conventional method. Abstract : Dimethyl carbonate (DMC) is a useful chemical and can substitute some toxic substances. The synthesis of DMC from methanol and urea is an attractive route, but is a thermodynamically unfavourable reaction. Enhancing the equilibrium conversion of the reaction is an intereting topic. In this study, we demonstrate that poly(ethylene glycol) diglyceryl ether (PEGDE, a poly(ethylylene glycol) based bis-diol), which is a non-toxic and cheap polymer, can be used as a functional medium for the synthesis of DMC from methanol and urea using ZnO as the catalyst. In the PEGDE/ZnO catalytic system, PEGDE reacted with urea to form poly(ethylene glycol) di(2, 3-carbonate glyceryl) ether (PEGDC), and the reaction equilibrium was shifted by sweeping away the generated ammonia. Then, DMC was produced after methanol was added and PEGDE was regenerated and the PEGDE/ZnO catalytic system could be reused directly. It was shown that a very high equilibrium yield could be achieved.